Holloway, Mary (audio interview #1 of 3) - Holloway, Mary (2/8/1882 - 3/1/1985); Price, Aleta, interviewer
INTERVIEW DESCRIPTION - The audio quality of this first, short interview with Mary Magdalena Holloway is poor because of background noise, including the sound of her rocking chair. This is coupled with the crackly voice of a fragile 92 year old. Nevertheless, except when noted, she can be understood. The interviews with Holloway were conducted by a student in a UCLA women's oral history class. 2/21/1974